Pulsed multireservoir engineering for a trapped ion with applications to state synthesis and quantum Otto cycles - W S Teixeira; M K Keller; F L Semião (New Journal of Physics, 2022)
Conducting an open quantum system towards a desired steady state through reservoir engineering is a remarkable task that takes dissipation and decoherence as tools rather than impediments. Here we develop a collisional model to implement reservoir engineering for the one-dimensional harmonic motion of a trapped ion. Our scheme is based on the pulsed interaction between the vibrational mode and the electronic levels of a trapped ion, which is promoted by resolved-sideband lasers. Having multiple internal levels, we show that multiple reservoirs can be engineered, allowing for more efficient synthesis of well-known non-classical states of motion and the generation of states that are unfeasible with a single-bath setup, for instance, thermal states with arbitrary positive temperatures. We apply these ideas to quantum Otto cycles beyond purely thermal reservoirs. In particular, we present general conditions for the violation of the standard Otto bound in the limiting regime of non-adiabatic dynamics.